Productive performance and ruminal variables of lambs fed urea-treated maize stover - Martínez-Trejo, Guillermina; Ortega-Cerrilla, Ma. Esther; Landois Palencia, Luis L.; Pineda Osnaya, Armando; Pérez Pérez, Jorge (Revista Mexicana de Ciencias Agrícolas, 2018)
The objective of this study was to investigate the effect of feeding lambs with maize stover treated with urea or supplemented with urea diluted or mixed in the feed. Daily feed intake (DFI), daily weight gain (DWG), and feed conversion (FC) were determined, as well as dry matter (DM), organic matter (OM), crude protein (CP), cell wall (CW), cell content (CC), cellulose (CEL) and hemicellulose (HEM) in vivo digestibility, rumen pH (pH), rumen ammonia (CRA), volatile fatty acids concentration (VFA), and in vitro degradability of dry matter (DDM). Four treatments were randomly assigned to 20 male Criollo sheep (20 ± 5 kg) in a completely randomized design. Diets fed to animals contained 30% concentrate and 70.0% of either untreated maize stover (UM); treated with urea (TM) (4 kg of diluted urea in 20 L of H2O 100-1 kg of maize stover, treated for 30 days); supplemented with diluted urea (SM) (38g de urea 50 mL-1 H2O), or urea mixed in the feed (MM) (38g animal-1day-1) at the moment lambs were fed. The addition of urea did not affect DFI, DWG, or FC. In vivo digestibility of DM, OM, CW, HEM and CEL was higher (p 0.05) for rumen pH and VFA concentration. CRA and in vitro degradability at 24, 48, and 72 h, were higher in the diets containing urea.
Keywords: lambs; maize stover; urea